Combining Group Compromised Price with bundle search strategies - Boongasame, Labor; Boonjing, Veera; Thipakorn, Bundit (My University, 2005)
This paper proposes combining the buyer coalition strategy, called Group Compromised Price, with bundle search strategy to obtain the greater discounts from forming a coalition that gives the number of buyers as large as possible. Copyright 2005 ACM.
Keywords: bundle search; coalition formation; e-commerce; group buying